LEGAL JURISDICTION AND PLACE OF OCCURENCE IN TRANSNATIONAL CYBERCRIME: A NORMATIVE ANALYSIS OF GLOBAL LAW AND INDONESIAN TELECOMMUNICATIONS REGULATIONS - Agustinus Nicholas L Tobing; Annisa Fitria (Awang Long Law Review, 2026)
This study investigates the establishment of legal authority and the site of the offense in international cyber offenses via a normative legal method, emphasizing global legal viewpoints such as the Budapest Convention, UN Convention against Cybercrime 2024, and Tallinn Manual 2.0, along with Indonesia’s domestic information technology laws including Law No. 11 of 2008 on Electronic Information and Transactions (UU ITE) with its revisions, and Law No. 27 of 2022 on Personal Data Protection (UU PDP). The foundation stems from the rising worldwide cyber risks that transcend borders, with BSSN records noting over 5,000 occurrences in Indonesia in 2025, while the issue formulation encompasses the layered definition of the site of the offense and cross-country investigative authority based on global concepts and examples like cyber assaults on Taiwan (2024-2025), INTERPOL reports on African cyber offenses (June 2025), and INTERPOL financial activities (September 2025). The research approach includes gathering secondary materials such as legal texts and official documents, employing statutory, comparative, and case evaluations to yield practical suggestions like ratifying international conventions, developing judicial guidelines, and establishing a national task force. The outcomes highlight the adjustment of authority theories for intangible cyber spaces, including three site of offense concepts (locus actus, effectus, instrumentum), and advocate for alignment to address regulatory voids, provide assurance, and safeguard state interests in the digital age.